Students attitudes towards new academic calendar / Halimatul Saadiah Osman - Osman, Halimatul Saadiah (2011)
In improving the quality of education in our country, Ministry of Education has introduced several approaches for our education in order for Malaysia to be on par with other countries. The introduction of the new session does not only focus on the primary education but also focuses on higher education. In achieving the government’s desire to make Malaysia on par with other countries, Ministry of Higher Education has introduced several important policies and organized several programs for higher education. In 2011, Ministry of Higher Education, Datuk Seri Mohd Khaled Nordin has dissolved and changed academic calendar for IPTA 2011-2012 session. This effort is consistent with government’s desire to make Malaysia a hub of education choice, particularly among foreign students at the regional and international.